Alteration of Fatty Acid Metabolism is Associated with Alzheimer's Disease in People with Down Syndrome. (20th December 2022) - Mapstone, Mark; ,
Abstract: Background: People with Down syndrome (DS) are at high risk for Alzheimer's disease (AD) in part because nearly all carry an extra copy of the APP gene which results in overexpression of amyloid. However, other factors are likely to interact with this genetic risk to produce individual pathobiological and clinical trajectories. We sought to examine the impact of diverse physiological pathways on AD risk in people with DS using plasma metabolomics. Method: We studied the plasma metabolome of 744 people with DS (mean age =49) using mass spectrometry (MS). A total of 144 individuals from our cohort met criteria for MCI or AD (DS‐AD, mean age= 55.0) and 600 were cognitively stable (DS‐NAD, mean age = 47.4). We quantified the relative abundance of over 7000 putative metabolites. We performed differential expression (DE) analysis and constructed group classification models (DS‐AD vs DS‐NAD) using Regularized Logistic Regression with age included as a covariate. We evaluated the classification models using Receiver Operating Characteristic (ROC) analysis. Result: We found 20 DE features between the DS‐AD and DS‐NAD groups (q < 0.05), of which we definitively identified 11 through tandem mass spectrometry. Of the 11 metabolites, 5 were naturally occurring unique human metabolites involved in fatty acid metabolism, including two diacylglycerides, one monoglyceride, one lysophosphatidycholine, and one acylcarnitine. When combined, this set of lipids classified the DS‐AD and DS‐NAD groups with ROC area under the curve of 0.796 [95% CI: 0.784‐ 0.808] across resamples (Sensitivity 29%, Specificity 97%). The addition of participant sex or APOE status did not significantly alter classification performance. Conclusion: Here, we find depletion of lipids in the plasma of people with DS who also have AD compared to people with DS who are not demented. While the overall number of DE metabolites is small, it is remarkable that from over 7000 putative metabolites measured, all are lipids involved in fatty acid metabolism. These results are consistent with an emerging picture of dysregulated lipid metabolism in AD, both in the people with DS and in the neurotypical population.